Ibero-American Bioethics
XX, 397 p. 3 illus.
Keywords: IBERO-AMERICAN BIOETHICS: History and Perspectives is a landmark work, collecting the voices of those who participated in the founding and development of bioethics in Latin America, the Caribbean, and the Iberian Peninsula. The volume offers the reader a cluster of perspectives on the various births of bioethics in this region. The essays in part are irreplaceable first-person voices that give an account of how bioethics took shape within the Spanish and Portuguese cultures both in Europe and in the Americas. As such, the volume is a collection of primary sources, otherwise not available in English, that presents historical panoramas and explores the new perspectives born of the different phases of bioethics in Ibero-America - from its assimilation of bioethics to its creation of its own authentic voices. The volume also encompasses critical reflections from this region on the quite different ways in which its local bioethics have taken shape. As such, this volume also offers an introduction into the quite different concerns that frame and direct bioethics in the cultural context of Ibero-America. The book gives a rich, deep, broad, and pluralist presentation of Ibero-American bioethics and its contribution to the international phenomenon of bioethics. It is a volume for all readers interested in bioethics, Ibero-American studies, and international approaches to health care policy.